2013
DOI: 10.1242/dev.097360
|View full text |Cite
|
Sign up to set email alerts
|

Bmp signaling repressesVegfato promote outflow tract cushion development

Abstract: SUMMARYCongenital heart disease (CHD) is a devastating anomaly that affects ~1% of live births. Defects of the outflow tract (OFT) make up a large percentage of human CHD. We investigated Bmp signaling in mouse OFT development by conditionally deleting both Bmp4 and Bmp7 in the second heart field (SHF). SHF Bmp4/7 deficiency resulted in defective epithelial to mesenchymal transition (EMT) and reduced cardiac neural crest ingress, with resultant persistent truncus arteriosus. Using a candidate gene approach, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 40 publications
2
45
0
Order By: Relevance
“…Although endothelial cell density in epithelial-specific Smad1/5 dKO was comparable to that of control thyroid glands, expression of endothelial cell identity markers (Cdh5, Pcdh12 and Tie1) and endothelial-enriched basement membrane proteins (type IV collagen α1, α2 and laminin α3) was impaired, consistent with ongoing reciprocal paracrine communications between epithelial and endothelial cells (Hick et al, 2013). In this report, we further found that BMP-Smad signaling in thyroid epithelial cells controls the expression of Vegfa, in agreement with reports in other cell types (Bai et al, 2013;Deckers et al, 2002;Shao et al, 2009;Shimizu et al, 2012). Of note, this regulation in zebrafish could be either positive (for Smad1) or negative (for Smad5) (He and Chen, 2005).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although endothelial cell density in epithelial-specific Smad1/5 dKO was comparable to that of control thyroid glands, expression of endothelial cell identity markers (Cdh5, Pcdh12 and Tie1) and endothelial-enriched basement membrane proteins (type IV collagen α1, α2 and laminin α3) was impaired, consistent with ongoing reciprocal paracrine communications between epithelial and endothelial cells (Hick et al, 2013). In this report, we further found that BMP-Smad signaling in thyroid epithelial cells controls the expression of Vegfa, in agreement with reports in other cell types (Bai et al, 2013;Deckers et al, 2002;Shao et al, 2009;Shimizu et al, 2012). Of note, this regulation in zebrafish could be either positive (for Smad1) or negative (for Smad5) (He and Chen, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…4B), but expression of Vegfr2, Pecam1 and endothelial cell-specific molecule 1 (Esm1) was normal. Vegfa controls endothelial cell development and BMP-Smad1/5 signaling is known to control Vegfa expression in several cell types (Bai et al, 2013;Deckers et al, 2002;Shao et al, 2009;Shimizu et al, 2012). We measured Vegfa in developing Smad1/5 dKO thyroids and found that it was reduced starting at E14.5; this reduction reached statistical significance starting at E16.5 (Fig.…”
Section: Smad1/5 Inactivation Impairs Thyroid Folliculogenesismentioning
confidence: 91%
“…Instead, Wnt1-Cre-targeted cardiac NCCs contributed to the semilunar valve leaflets and septal bridge ( Figure 3A). In the Tie2-Cre lineage-traced OFT, many individual YFP-positive cells were present in the endocardial cushions ( Figure 3A), consistent with the previously described contribution of endoMT-derived cells to the endocardial cushions (17)(18)(19). Tie2-Cre lineage-traced cells also contributed to the semilunar valves ( Figure 3A).…”
Section: Introductionsupporting
confidence: 89%
“…To show that endoMT was reduced in the OFT of mice lacking NRP1 in vivo, we investigated the expression of the transcription factor Slug, a well-established effector of endoMT (42,43). We first performed reverse-transcription PCR (RT-PCR) analysis signaling lacking NCC-derived SEMA3C display disorganized endocardial cushions and lack proximal OFT septation, 2 processes known to rely on endoMT (17)(18)(19). We therefore investigated whether cardiac NCC immigration and the onset of endoMT correlate during OFT development.…”
Section: Nrp2mentioning
confidence: 99%
“…This Cre line has been extensively utilized to delete genes for investigation of the SHF development in mice (Ai et al, 2007;Bai et al, 2013;Engleka et al, 2012;Xie et al, 2012). Using Mef2c-Cre, Pten was deleted in the SHF.…”
Section: Deletion Of Pten In the Shf Progenitors Results In Shf Expanmentioning
confidence: 99%